LATE MIOCENE PALEOGEOGRAPHY OF THE MONTE SOLDANO AREA, SOUTHEASTERN PART OF VOLTERRA BASIN, TUSCANY, ITALY (Rivista italiana di Paleontologia e Stratigrafia, 1995)
Several Upper Tortonian to Lower Messinian sedimentary facies were recognized and mapped in the M.te Soldano area at the southeastern end of the extensional Basin of Volterra in the Nothern Apennines in Tuscany. They consist of (a) disorganized coarse  conglomerates, ft) organized conglomerates interbedded with sandstone, (c) coarse to medium grained sandstone which is present both as interlayers within the organized conglomerares as well as turbidite layers interbedded with lacustrine clay,(d) marlstone rich in opercula of Bithynia, and (e) lacustrine clay with few sandy turbidite interlayers. The vertical and lateral distribution of these facies indicates the existence of a large alluvial fan complex. The development of such a large complex from an apparently relatively narrow sediment source area (an interbasin ridge) was possible because the feeding rivers were probably located at the intersection between a border fault and a fault associated with a transfer zone. This allowed for a much wider drainage basin.